IDENTIFIKASI PARASIT CACING NEMATODA GASTROINTESTINAL PADA SAPI BALI (Bos sondaicus) DI DESA TAMAN AYU KABUPATEN LOMBOK BARAT - Supriadi Supriadi; Muhammad Khozin Kutbi; Seli Nurmayani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
Nematoda worms are one of the helminth groups that have wide distribution in ruminants. Various types of nematoda worms are known as cattle parasites and have affected their health. The aim of this research was to determine the species of gastrointestinal nematoda worms in cattle that were farmed in Taman Ayu Village, Gerung Subdistrict, West Lombok District. A total of 115 stool samples were collected by random sampling from February to August 2018 in 3 sub-village that have high cattle population in Taman Ayu Village. Sampling was carried out by random sampling method in dairy cattle. Fecal samples were examined using native and standard flotation technique to determine the number of species of gastrointestinal nematoda worms. Flotation method was depeloved by employing sugar absolut solution. The results of the examination of the samples have shown 8 species of nematoda parasite worms such as Strongyloides papillosus, Trychosrtongylus sp., Haemonchus contortus, Toxocara vitulorum, Trichuris spp, Nematodirus spp., Capillaria spp., Oesophagostomum spp. and larvae. Strongyloides papillosus is the species with the highestnumber of infection due to it can be transmitted by autoinfection in the same individual. The farmers limited knowledge about good dairy systems and bad sanitation of cattle farm contribute to high numbers of nematoda worms in fecal samples. It is necessary for farmers to maintain best management dairy systems. Furthermore, routine treatment by anthelmintic will help farmers to protect cattles from the infection.